2021
DOI: 10.31579/2692-9562/033
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients Correctly Use Steroid Nose Spray? A Patient-Reported Survey of the Nasal Spray Technique and Patient Compliance

Abstract: Background:Correct nasal spray techniqueand patient compliance are the two mostimportant factors in the use of steroid nose spray. Objectives:To find out if patientsuse steroid nasal spray with a correctspray technique and if they are compliant in using the spray. Design: Patient-reported survey Participants: 100 participants (1 excluded) Main outcome measures 1) Nasal spray technique 2) Patient compliance Results: Out of 99 participants included in this study only one patient used steroid nose spray with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Nevertheless, the results of this survey clearly showed that fear of side effects may influence appropriate prescription. The need to instruct patients on proper application technique in order to limit side effects and improve adherence to therapy should be emphasized as noted by other authors [ 23 ]. In case of side effects despite due precautions, a change in modality of administration—or adjuvant—action should be taken.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the results of this survey clearly showed that fear of side effects may influence appropriate prescription. The need to instruct patients on proper application technique in order to limit side effects and improve adherence to therapy should be emphasized as noted by other authors [ 23 ]. In case of side effects despite due precautions, a change in modality of administration—or adjuvant—action should be taken.…”
Section: Discussionmentioning
confidence: 99%